Experience of diagnosing and managing a patient with spinal Rosai-Dorfman-Destombes disease in a tuberculosis hyperendemic region - Ming, Han Tan; Choong, Hoon Foo; May Honey Ohn; Khin Maung Ohn (BMJ Publishing Group, 2022)
Classic Rosai-Dorfman-Destombes disease (RDD) is a rare histiocytic disorder with bilateral massive painless cervical lymphadenopathy. It is a mysterious disease and there is little knowledge of its pathogenesis, clinical features, radiological findings, laboratory investigations, effective treatments and prognosis. Some of its clinical presentations may overlap with those of Mycobacterium tuberculosis infection. Just like tuberculosis infection, RDD may involve many other organs, for example, skin, kidney, bone, brain and spine. The diagnosis can easily be overlooked, especially in communities hyperendemic to tuberculosis infection. We report our experience in diagnosing and managing a patient with spinal RDD with concurrent tuberculosis infection, who was treated empirically for cervical tuberculous lymphadenitis without a conclusive laboratory finding prior to her spinal condition. In view of her acute neurological deficit, emergency spinal decompression was performed. Her intraoperative spinal samples had shown classic histopathological features of RDD. We believe the lymphadenopathy was part of the clinical presentation of RDD. She showed favourable neurological recovery throughout the follow-up.